Comparative assessment of the Euglena gracilis var. saccharophila variant strain as a producer of the β‐1, 3‐glucan paramylon under varying light conditions. Issue 4 (19th July 2018) - Sun, Angela; Hasan, Mafruha Tasnin; Hobba, Graham; Nevalainen, Helena; Te'o, Junior
Abstract : Euglena gracilis Z and a "sugar loving" variant strain E. gracilis var. saccharophila were investigated as producers of paramylon, a β‐1, 3‐glucan polysaccharide with potential medicinal and industrial applications. The strains were grown under diurnal or dark growth conditions on a glucose–yeast extract medium supporting high‐level paramylon production. Both strains produced the highest paramylon yields (7.4–8 g · L −1, respectively) while grown in the dark, but the maximum yield was achieved faster by E. gracilis var. saccharophila (48 h vs. 72 h). The glucose‐to‐paramylon yield coefficient Ypar/glu  = 0.46 ± 0.03 in the E. gracilis var. saccharophila cultivation, obtained in this study, is the highest reported to date. Proteomic analysis of the metabolic pathways provided molecular clues for the strain behavior observed during cultivation. For example, overexpression of enzymes in the gluconeogenesis/glycolysis pathways including fructokinase‐1 and chloroplastic fructose‐1, 6‐bisphosphatase (FBP) may have contributed to the faster rate of paramylon accumulation in E. gracilis var. saccharophila . Differentially expressed proteins in the early steps of chloroplastogenesis pathway including plastid uroporphyrinogen decarboxylases, photoreceptors, and a highly abundant (68‐fold increase) plastid transketolase may have provided the E. gracilis var. saccharophila strain an advantage in paramylon production during diurnal cultivations. In conclusion, the variant strain E. gracilis var. saccharophila seems to be well suited for producing large amounts of paramylon. This work has also resulted in the identification of molecular targets for future improvement of paramylon production in E. gracilis, including the FBP and phosophofructokinase 1, the latter being a key regulator of glycolysis.